Mechanical characteristics and hydrophobicity of alkyl ketene dimer compatibilized hybrid biopolymer composites - Caylak, Sena; Ertaş, Murat; Cavdar, Ayfer Donmez; Angin, Naile (Wiley, 2021)
In this study, the effect of alkyl ketene dimer (AKD) on the mechanical and physical properties of natural fiber (NF) and glass fiber (GF) reinforced poly(lactic acid) (PLA) composites were investigated in detail. The hybrid PLA composites were manufactured by extrusion method followed by hot press molding. AKD was used to improve the hydrophobicity of hybrid PLA composites and compatibility of NF and PLA in the polymer matrix. The tensile and flexural tests, thickness swelling, water absorption, and contact angle measurements were accomplished for determining the performance of the hybrid PLA composites. The surface morphology of the hybrid PLA composites was also performed by scanning electron microscopy. The incorporation of AKD and NF into PLA matrix improved the mechanical strengths by 40% and above compared to those of samples without AKD. But, tensile and flexural moduli decreased as 7% and 14% of the samples with NF and AKD, respectively. Contact angle was higher for the hybrid PLA composites with AKD compared with the composites without AKD. However, the results revealed that in the presence of GF, AKD had no significant effect on overall properties of the hybrid PLA composites. In the light of the findings, AKD may have a potential usage as coupling agent in the NF filled PLA composites.
Keywords: alkyl ketene dimer; biodegradable polymers; glass fiber; natural fiber; poly(lactic acid)